Analisis Pelaksanaan Pembelajaran PJOK Materi Beladiri di SMA se-Kecamatan Mranggen (Indonesian Journal for Physical Education and Sport, 2022)
This study aims to find out how teachers in Mranggen implement PJOK learning on self-defense materials. This study uses a qualitative descriptive method, where the research instrument is the researcher himself. Data collection techniques are interviews, observation, and documentation. The data analysis techniques used are data reduction, data display, and drawing conclusions. Martial arts is a compulsory subject at the high school level and an easy subject to implement, but the fact is that there are still many teachers who do not carry out learning PJOK martial arts at the high school level. The result of the research is that researchers only examined 3 schools that carried out martial arts learning because here the focus of the researchers was to analyze the implementation of school learning that carried out learning martial arts materials. The conclusion is that learning PJOK martial arts in high schools throughout the Mranggen sub-district at 3 research target schools that carry out learning in terms of planning, implementation, and evaluation is still not good, there are 2 out of 3 schools that do not meet the standards of learning implementation which can be seen from each sub indicator. Suggestions given by teachers should be to complete learning tools and understand the guidelines for making appropriate learning tools, and teachers are expected to immediately follow PPG.